PENINGKATAN DAYA SAING USAHA OLAHAN PANGAN (PEYEK KACANG DAN EMPING MELINJO) - Rita Kusumawati; Taufik Akhbar; Alien Akmalia (Universitas Muhammadiyah Tapanuli Selatan, 2021)
This programe aims to help partners to be more independent and improve their business competitiveness. Business partners in this program are Peyek Bu Dalidjo and melinjo chips